A novel methodology for assessing laryngeal and vagus nerve integrity in patients under general anesthesia. Issue 7 (July 2017) - Sinclair, Catherine F.; Téllez, Maria J.; Tapia, Oscar R.; Ulkatan, Sedat; Deletis, Vedran
Highlights: We present the laryngeal adductor reflex as a new intraoperative monitoring method for laryngeal and vagus nerves. This method relies on endotracheal tube electrodes for stimulating and recording laryngeal responses. This technique monitors the entire vagal reflex arc, including sensory, motor and brainstem pathways. Abstract: Objective: To describe a novel methodology for intraoperative neuro-monitoring of laryngeal and vagus nerves by utilizing the laryngeal adductor reflex (LAR). Methods: Case series of 15 patients undergoing thyroid and cervical spine surgeries under total intravenous general anesthesia. Vocal fold mucosa was electrically stimulated to elicit a LAR using endotracheal tube based electrodes. Contralateral R1 (cR1) and R2 (cR2) responses were recorded using the endotracheal tube electrode contralateral to the simulating electrode. Results: The LAR was reliably elicited in 100% of patients for the duration of each surgical procedure. Mean onset latency of cR1 response was 22.4 ± 2.5 ms (right) and 22.2 ± 2.4 ms (left). cR2 responses were noted in 10 patients (66.7%). No peri-operative complications or adverse outcomes were observed. Conclusions: The LAR is a novel neuro-monitoring technique for the vagus nerve. Advantages over current monitoring techniques including simplicity, ability to continuously monitor neural function without placement of additional neural probes and ability to assess integrity of both sensory and motor pathways. Significance: The LAR represents a novel method for intraoperatively monitoring laryngeal and vagus nerves. The LAR monitors the entire vagus nerve reflex arc and is thus applicable to all surgeries where vagal nerve integrity may be compromised.